The Effect of Red Beans Flour Substitution on The Glycemic Index of Cupcakes - Esthy Rahman Asih; Audya Nadya Rinaldi; Yessi Alza (JURNAL PROTEKSI KESEHATAN, 2019)
Red beans are a protein food source, so their role in improving nutrition is significant, besides being rich in protein, red beans are also a source of carbohydrates, fiber, vitamins, and minerals. Cupcake is a food made from flour and is widely favored by all groups. The purpose of this study is to discover the effect of the substitution of wheat flour with red bean flour on the sensory properties, protein content and glicemix index in the cupcake. The cupcake products with concentration treatments varying 100%: 0%, 40%: 60%, 50%: 50%, 60%: 40% have been hedonic tested. It can be concluded from the results of this study that the red bean cupcake with the best treatment was a concentration of 50%: 50% Based on the sensory properties of the cupcake on the color and taste, meaning that there was an influence from each treatment on the cupcake. The protein content of red bean cupcake on the selected product, was higher at 8.75% compared to 100% control of wheat flour at 7.49%. The glycemic index value on the selected red bean cupcakes was 58,1.